Her surprise cowboy groom - McDavid, Cathy, 1956- (Harlequin heartwarming, 2023)
An instant familyCould change her plans!Ambitious wedding dress designer Laurel Montgomery can't afford to be distracted...especially not by easygoing cowboy Max Maxwell. Wrangling his three-year-old twin daughters, a rambunctious puppy and a fledgling business, Max has his hands full, too. But he also knows the value of going for ice cream and fishing with his girls. Can he show Laurel there are more important things than making it big--like love and family? From Harlequin Heartwarming: Wholesome stories of love, compassion and belonging.